Investigating the Potential for Label‐Free Detection of Cell Apoptosis through Terahertz Nano‐Metasurfaces - Yeeun Roh; Jisung Kwak; Sang Jun Sim; Hyun Seok Song; Minah Seo (Advanced Photonics Research)
A label‐free method to monitor apoptosis in cells using a terahertz (THz) metasurface‐based biosensing platform is demonstrated. Apoptosis, a crucial process for eliminating damaged cells and preventing cancer, often dysregulates in cancer, leading to tumor formation. Measuring apoptosis directly in cells’ natural environment without labeling is a significant aim in cell biology. The platform leverages THz metasurfaces to detect H2O2‐induced apoptosis noninvasively, focusing on transmittance changes and frequency shifts to comprehensively analyze cellular dielectric properties. HEK293 cells treated with hydrogen peroxide (H2O2), a natural inducer of oxidation stress across diverse cell types, are used to validate the system, demonstrating precise sensitivity to apoptosis without the need for chemical labeling or invasive treatments. The results show a clear correlation between apoptosis, measured via Cell Counting Kit‐8, and terahertz transmittance spectra. This approach offers a powerful combination of label‐free, nondestructive, and further real‐time apoptosis monitoring in cellular systems, highlighting its potential for diverse applications in cell biology and therapeutic research.